Synthesis and Characterization of Ce0.8Y0.2-xCaxO2-d as Electrolyte for Solid Oxide Fuel Cells - Tian, Changan; Yang, Jie; Li, Minghua; Yin, Qiyi; Ji, Bifa; Sun, Hong; Xie, Jinsong; Ma, Jinjin (Asian Journal of Chemistry, 2014)
In this study, ultrafine Ce0.8Y0.2-xCaxO2-d (x = 0 to 0.1) powders have been successfully prepared by the sol-gel method. The samples were characterized by TG-DSC, XRD and AC impedance. Experimental results indicated that highly phase-pure cubic fluorite electrolyte Ce0.8Y0.2-xCaxO2-d powders were obtained. The Ce0.8Y0.2-xCaxO2-d series electrolytes have higher relatively dense over 96 % can obtained after sintered at 1400 ºC. Among all the samples, Ce0.8Y0.1Ca0.1O1.85 shows excellent ionic conductivity of 0.041 S/cm measured at 800 ºC and lower conductive activation energy of 0.89 eV.